Teaching Technology in Learning Process of Speaking Ability by Using Fondi Application - Erlita, Yeni; Putri, Aryanti Anna (LingPoet: Journal of Linguistics and Literary Research, 2024)
The most important purpose of today's technology is to make all people smart and independent, particularly students, in education. This study investigates the subject of teaching technology in the teaching and learning process by Fondi application. Fondi is an application that contains a virtual world where users seem to live in a city and can communicate with fellow users by going to various places and meeting new acquaintances, where users can practice their conversational skills. The use of the Fondi application is to make students can fluent and confident in speaking English. Besides being able to improve students' speaking skills, they can also maximize the use of technology as a very effective learning tool for all parties. The participant of this study was 35 students. A qualitative research design was employed with instruments, interviews, observation, and recording. In investigating the use of the Fondi application to increase students' ability, the Fondi application to increase students' speaking ability as a media in SMP Imelda Medan. It focuses on speaking ability in the learning process. The result of this study showed a positive, based on the usefulness accessibility of its application was 98% positive based on features the accessibility.